2013
DOI: 10.1007/s00415-012-6828-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical determinants of primary and secondary fatigue in patients with Parkinson’s disease

Abstract: Clinical and psychosocial factors associated separately with primary and secondary fatigue in Parkinson's disease (PD) patients have not been thoroughly studied before. The aim of our study was to assess factors associated with different fatigue domains in groups with primary and secondary fatigue in PD separately. We divided 165 nondemented PD patients according to the absence/presence of depression, anxiety and excessive somnolence into groups with primary fatigue (N = 63) and with secondary fatigue (N = 102… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 46 publications
3
37
1
2
Order By: Relevance
“…However, fatigue in PD is generally considered to be a non-dopaminergic symptom. In fact, most studies have thus far not found any significant association between dopaminergic treatment or daily L -dopa equivalent dose and fatigue [24,28,53]. Similarly, we did not find an association between fatigue and dopaminergic medication in our study (results not shown).…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…However, fatigue in PD is generally considered to be a non-dopaminergic symptom. In fact, most studies have thus far not found any significant association between dopaminergic treatment or daily L -dopa equivalent dose and fatigue [24,28,53]. Similarly, we did not find an association between fatigue and dopaminergic medication in our study (results not shown).…”
Section: Discussioncontrasting
confidence: 52%
“…Our results show that more symptoms of depression are associated with reduced motivation, and that symptoms of depression mediate the impact of worse functional status on mental fatigue, reduced activity and general fatigue. As was found in the study of Skorvanek et al [28], PD patients with depression had both higher UPDRS-III scores and fatigue scores in all fatigue domains compared with primary fatigue; however, once depressed patients were selected, depression did not play a further role in determining fatigue in this group of patients. Their findings are in accordance with some other studies, which have found worse motor and fatigue symptoms in depressed patients [59].…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Если раньше этот симптом считался особен-ностью развернутых стадий заболевания, то сейчас пока-зано, что утомляемость может появляться уже на ранних стадиях БП примерно у 1 / 3 пациентов [70]. В зависимости от методологии исследования частота утомляемости коле-блется от 28 до 77,6% [68,[71][72][73][74][75].…”
unclassified